2016
DOI: 10.1016/j.jtusci.2015.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity and phytochemical constituents of marine red seaweeds (Jania rubens,Corallina mediterraneaandPterocladia capillacea)

Abstract: of marine red seaweeds (Jania rubens, Corallina mediterranea and Pterocladia capillacea), J. Taibah Univ. Sci. (2015), http://dx. AbstractSeaweeds are potential renewable resources in the marine environment. The antibacterial activity of Jania rubens, Corallina mediterranea and Pterocladia capillacea were analyzed against human pathogenic bacteria. The present study was performed to investigate the phytochemical constituents of seaweeds, such as alkaloids, flavonoids, steroids, terpenoids and phlobatannins. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(68 citation statements)
references
References 33 publications
0
60
0
Order By: Relevance
“…Specifically, n-hexadecanoic acid represented the phytocomponent with the lowest concentration among the entire phytocomponents present in AqEUF of C. papaya. Tetradecanoic acid (myristic acid) has been detected in methanolic leaf extracts of J. rubens, C. mediterranea and P. capillacea [26], L. inermis [36] and hexane/acetone leaf extracts of M. edule [29]. Previous studies showed that tetradecanoic acid was the major antibacterial and antioxidant principles isolated from Myristica fragrans (nutmeg) [39,40] as well as antibacterial agent from P. capillacea [41].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, n-hexadecanoic acid represented the phytocomponent with the lowest concentration among the entire phytocomponents present in AqEUF of C. papaya. Tetradecanoic acid (myristic acid) has been detected in methanolic leaf extracts of J. rubens, C. mediterranea and P. capillacea [26], L. inermis [36] and hexane/acetone leaf extracts of M. edule [29]. Previous studies showed that tetradecanoic acid was the major antibacterial and antioxidant principles isolated from Myristica fragrans (nutmeg) [39,40] as well as antibacterial agent from P. capillacea [41].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, octadecanoic acid, 2,3-dihydroxypropyl ester, which is an analogue of hexadecanoic acid, 2,3-dihydroxypropyl ester, is present in marine red seaweeds such as Pterochadia capillacea and was noted to exhibit antibacterial activity [26]. Additionally, hexadecanoic acid, 2,3-dihydroxypropyl ester is present in methanolic leaf extract of Spermacoce articularis, which is an important medicinal plant used in Indian folk medicine [27], as well as in chloroform extracts of mosses (Polytrichum commune and Rhytidiadelphus triquetrus), noted for their antimicrobial activity and anticancer activity on cancer cell lines [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Green seaweed samples H2O2 activity was about 30% 15 . Maximum activity in methanolic extracted Corollina mediterrane, Pterocladia capillacea and Jania rubens 16 . Highest reducing power activity in aqueous extract of Scytosiphon lomentaria than in ethanol extract 17 .…”
Section: Discussionmentioning
confidence: 98%
“…11,13-Dihydroxy-tetradec-5-ynoic acid, methyl ester was previously identified in Citrullus colocynthis [16]. The other important compounds identified were cis-5,8,11,14,17-Eicosapentaenoic acid trimethylsilyl ester, which is omega 3 fatty acid and plays a vital role as an energy source, maintains membrane stability and cell signaling [17]. The compound 13 was identified as Columbin, a diterpenoid furane lactone, previously extracted from Calumbae radix reported to reduced azoxymethane-induced colon carcinogenesis gave m/z at 358 [18].…”
Section: Gc-ei/ms Profilingmentioning
confidence: 99%